2016
DOI: 10.2298/jas1603227t
|View full text |Cite
|
Sign up to set email alerts
|

Seedling growth of maize (Zea mays L.) inbred lines affected by seed treatment with pesticides

Abstract: Seed treatment is a common way of fungicide and insecticide use nowadays, since this way of pesticide application can provide the best protection in the vicinity of the future plant. The aim of research was to evaluate the effects of different seed treatments on germination and seedling growth in three maize inbred lines. The research included the seed treatment with several combinations of a fungicide Maxim XL 035-FS (a.i. metalaxil-M + fludioxonil) and neonicotinoid insecticides Gaucho 600-FS (a.i. imidaclop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This trend was clear as we proceed with years of storage from year 2 to year 8 (Tables 2-5). Tamindzic et al (28) stated that the fungicide cruse could be has stimulant effect in seed viability. Deterioration after one year was clear and revealed, showing that the fungicide could lose some of its efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…This trend was clear as we proceed with years of storage from year 2 to year 8 (Tables 2-5). Tamindzic et al (28) stated that the fungicide cruse could be has stimulant effect in seed viability. Deterioration after one year was clear and revealed, showing that the fungicide could lose some of its efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported by many authors, although for different crops, that thiamethoxam and imidacloprid can express phytotoxic effects and negatively affect germination and plant growth, when applied directly on seeds (Wilde et al, 2001;Castro et al, 2008;Stevens et al, 2008, Mrđa et al, 2011a. However, Tamindžić et al (2016) concluded that these two active ingredients did not adversely affect seed germination of several maize inbred lines, moreover they had a positive impact on the root growth.…”
Section: Discussionmentioning
confidence: 99%
“…Seeds are susceptible to damage by insecticides and fungicides [4][5][6]; thus, when employed, it is important to carefully control the exposure period and dose. Furthermore, when used on edible grains, intoxication by the consumer must be avoided.…”
Section: Introductionmentioning
confidence: 99%